2013
DOI: 10.1016/j.ajhg.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Defects in the Motor Adaptor BICD2 Cause Proximal Spinal Muscular Atrophy with Autosomal-Dominant Inheritance

Abstract: The most common form of spinal muscular atrophy (SMA) is a recessive disorder caused by deleterious SMN1 mutations in 5q13, whereas the genetic etiologies of non-5q SMA are very heterogeneous and largely remain to be elucidated. In a Bulgarian family affected by autosomal-dominant proximal SMA, we performed genome-wide linkage analysis and whole-exome sequencing and found a heterozygous de novo c.320C>T (p.Ser107Leu) mutation in bicaudal D homolog 2 (Drosophila) (BICD2). Further analysis of BICD2 in a cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 38 publications
5
122
0
Order By: Relevance
“…Studies in rodents have shown that this protein plays an important role in dynein-based cargo transport in neurons (32)(33)(34). Consistent with these findings, missense mutations in the human BICD2 gene are also associated with SMALED (35)(36)(37) and cortical malformations (38,39). The protein uses an N-terminal coiled-coil domain (BICD2N) to bind dynein and dynactin and a C-terminal coiled coil (BICD2C) to bind cargos (17).…”
Section: Significancesupporting
confidence: 49%
“…Studies in rodents have shown that this protein plays an important role in dynein-based cargo transport in neurons (32)(33)(34). Consistent with these findings, missense mutations in the human BICD2 gene are also associated with SMALED (35)(36)(37) and cortical malformations (38,39). The protein uses an N-terminal coiled-coil domain (BICD2N) to bind dynein and dynactin and a C-terminal coiled coil (BICD2C) to bind cargos (17).…”
Section: Significancesupporting
confidence: 49%
“…1 Recently, BICD2 has been identified to cause dominant SMA. [1][2][3] Here, we provide additional evidence that BICD2 is a cause of dominant SMA and report detailed clinical, electrophysiological and MRI data from a three-generation family with cosegregation of a novel BICD2 mutation. These findings extend current notions of BICD2, demonstrating that it can present with adult-onset combined proximal and distal lower extremity SMA.…”
mentioning
confidence: 89%
“…These patients are characterized by non-progressive congenital or earlyonset lower-limb-predominant weakness, which often results in significant mobility impairment. Secondly, Peeters et al [68] found mutations in BICD2 in independent Bulgarian families with autosomal-dominant proximal SMA. First, Oates et al [67] reported several missense mutations in BICD2 in patients affected with DCSMA or DCSMA with upper motor neuron features, or HSP (hereditary spastic paraplegia).…”
Section: Mutations In Bicd2mentioning
confidence: 99%
“…Secondly, Peeters et al [68] found mutations in BICD2 in independent Bulgarian families with autosomal-dominant proximal SMA. Some experimental evidence exists: BICD2-R501P and BICD2-S107L mutants increase dynein-dynactin binding and the BICD2-Q774G mutant decreases Rab6 binding [67,68]. Thirdly, Neveling et al [69] described four BICD2 mutations in Dutch and Canadian families afflicted with autosomal-dominant SMA, with weakness and atrophy of proximal and distal muscles mainly of the legs.…”
Section: Mutations In Bicd2mentioning
confidence: 99%